PENERAPAN INTRAVENOUS (IV) BUNDLE CARE DENGAN KEJADIAN PLEBITIS DI ICU RUMAH SAKIT SUMBER WARAS JAKARTA - aprilian sugara, jeffry; Marisi, Esther Lenny Dorlan (Sekolah Tinggi Ilmu Kesehatan Sumber Waras, 2026)
Background: Phlebitis is a common Healthcare-Associated Infection (HAI) related to the use of Peripheral Intravenous Catheters (PIVCs), particularly in Intensive Care Unit (ICU) patients. Critically ill patients often require prolonged intravenous therapy, increasing the risk of intravenous complications. The implementation of Intravenous (IV) Bundle Care is an evidence-based strategy to reduce phlebitis through adherence to standard procedures during insertion and maintenance. Objective: This study aimed to identify nurses’ compliance with IV Bundle Care during insertion and maintenance and to describe the incidence of phlebitis among ICU patients at Sumber Waras Hospital, Jakarta. Methods: This study used an Evidence-Based Nursing (EBN) case study design. The sample consisted of five ICU patients receiving intravenous therapy via PIVC. Data were collected over three days through direct observation using an IV Bundle Care checklist and the Visual Infusion Phlebitis (VIP) Score. Data were analyzed descriptively. Results: Nurses’ compliance with IV Bundle Care during insertion reached 100% across all components. During maintenance, 100% compliance was observed in hand hygiene, insertion site care with transparent dressings, assessment of PIVC necessity, and patient or family education. Infusion set replacement was performed based on clinical indications in 60% of patients. VIP Score assessment showed that 80% of patients had no phlebitis, while 20% experienced early-stage phlebitis. Conclusion: High compliance with IV Bundle Care was accompanied by a low incidence of phlebitis among ICU patients. Consistent implementation supported by documentation and monitoring is necessary to maintain patient safety.